Strategy for Strengthening Bagha Utsaha Padruwen Customary Villages (Bupda) Through Professional Management and Local Wisdom (Lembaga Contrarius Indonesia, 2026)
The development of the people's economy in Bali cannot be separated from the role of traditional villages as socio-cultural institutions that possess economic potential based on local wisdom. One of the institutional innovations of traditional economics developed is the Baga Utsaha Padruwen Desa Adat (BUPDA), a village-owned enterprise that aims to manage local assets and economic potential for the welfare of the village community. This study aims to examine strategies for strengthening BUPDA through the implementation of professional management and the integration of Balinese local wisdom values. The research method used is empirical legal research, with a normative-empirical approach to the laws and regulations and customary law applicable in Balinese society. The results show that the existence of BUPDA has a strategic role in strengthening the traditional economy, but still faces challenges such as a weak internal legal basis (BUPDA pararem), low human resource capacity, and a lack of professional governance. The implementation of professional management based on the principles of transparency, accountability, and effectiveness is a key factor in strengthening BUPDA institutions. Furthermore, the integration of the values of Tri Hita Karana, Tat Twam Asi, Nyama Braya, and Tri Kaya Parisudha serves as the moral and spiritual foundation for BUPDA management, ensuring its continued rootedness in Balinese culture. Therefore, strengthening BUPDA through professional management and local wisdom is expected to achieve sustainable, competitive, and independent traditional village economies while maintaining Balinese social and cultural harmony.